Comunidades terapêuticas e o cenário da contrarreforma psiquiátrica brasileira - Sousa, Artur Bezerra Mota (Universidade Federal do Tocantins, 2023)
The present work is qualified in the theoretical reflection and review of the events that mark the growing movement of psychiatric counter-reform in progress in Brazil, highlighting the role played by the Therapeutic Communities to the facts under discussion. The conservative current that has occupied and has been taking strength in the national political scenario calls usto reflect on the discussions that are established against the reformist positions, representing an attempt to consolidate policies centered on the mercantilization of health through private initiative. The present work is composed, first of a brief historical review of the counter-reform movements, highlighting their flirtation with conservative political agendas. Next, an analysis of the dismantling processes suffered by RP is made through an awareness of the nefarious strategies of regulation of mental health policies, highlighting the strategy of commodification of mental health through Therapeutic Communities (TCs). The research of bibliographic review of qualitative character, carried out through documental means, selected the material for analysis available in the official sites of public management organs linked to the theme. The analysis of the research inputs was carried out through selected publications on the Virtual Health Library (VHL) and Scientific Electronic Library Online (SciELO) platforms. It concludes with a reflection on the already evident damages and those that may still occur, having as its axis the fundamental role of resistance in the face of the listed problems.